2015
DOI: 10.1016/j.prevetmed.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii seropositivity and associated risk factors in goats in Ontario, Canada

Abstract: Coxiella burnetii is a zoonotic bacterium, and infection in goats with this bacterium can result in abortion, stillbirth or birth of non-viable kids. A cross-sectional study was conducted to identify the seroprevalence and risk factors for C. burnetii exposure in Ontario goats. Sera were collected between August 2010 and February 2012, and tested for C. burnetii specific antibodies using an enzyme-linked immunosorbent assay (IDEXX). Overall, 63.2% (48/76, 95% CI=51.9-73.4) of farms had one or more seropositive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…In Indiana, USA, no significant difference in seropositivity was found between milk and meat goat breeds (BAUER et al, 2016). In Ontario, Canada, where intensive breeding is more common and the presence of the microorganism may be more prevalent, a higher prevalence of seropositivity was reported among milk goats (MEADOWS et al, 2015b). However, a study in Kenya carried out by Muema et al (2017) found that animals raised in a pastoral nomadic system (similar to extensive farming) were three times more likely to test seropositive for C. burnetii than animals in other systems like mixed farming.…”
Section: Discussionmentioning
confidence: 96%
“…In Indiana, USA, no significant difference in seropositivity was found between milk and meat goat breeds (BAUER et al, 2016). In Ontario, Canada, where intensive breeding is more common and the presence of the microorganism may be more prevalent, a higher prevalence of seropositivity was reported among milk goats (MEADOWS et al, 2015b). However, a study in Kenya carried out by Muema et al (2017) found that animals raised in a pastoral nomadic system (similar to extensive farming) were three times more likely to test seropositive for C. burnetii than animals in other systems like mixed farming.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have investigated risk factors of coxiellosis in ruminants in the past decade . Factors that were associated with lower risk of seropositivity in ruminants in these studies included quarantine of new animals entering the farm, use of stringent hygiene measures for visitors, limited introduction of new animals, prompt removal of birth materials immediately postpartum, and frequent cleaning or changing of bedding.…”
Section: Control Of Coxiellosismentioning
confidence: 99%
“…Recommendations regarding disinfection are described below. Routine cleaning and disinfection of lambing/kidding pens has been demonstrated to be associated with a lower risk of human seroconversion in producers . During this cleaning on farms with documented coxiellosis it is recommended that a fit tested N95 mask be used, and essential if another individual developed Q fever.…”
Section: Zoonotic Risks and Mitigation Strategiesmentioning
confidence: 99%
“…The higher seroprevalence consistently found in sheep as compared to cattle in the Eastern Pyrenees are in accordance with previous reports in semi-extensive and extensive grazing systems [ 17 ]. High C. burnetii seroprevalence with zoonotic risk has been reported in goats [ 12 , 13 , 18 , 19 ], but the low sample size of our study does not allow to draw strong conclusions. However, the absence of seropositive goats, altogether with the low goat population and the few goats per herd in the study area [ 10 ], do not allow to point to this species as important for C. burnetti spread in the Eastern Pyrenees.…”
Section: Resultsmentioning
confidence: 65%